(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
The present study evaluated the effectiveness of the moral behavior intervention for children who attended the governmental program "Escola da Família" (PEF). Participants were five children, seven and ten years old, who showed behavior problems and weekly attended the PEF. The intervention consisted of the application of a moral behavior program, with 13 sessions that approached themes related to virtues. The participants’ evaluation was conducted through the pre and post-test Child Behavior Checklist (CBCL). The averages of the participants’ raw scores were statistically compared, and individual scores also were analyzed. All participants showed an increase in the social competences and a decrease in the behavior problems, when comparing the averages and individual CBCL scores, before and after the intervention. The moral behavior program was effective to promote social competences and to reduce behavior problems for participants from PEF.